(untitled) (Research, Society and Development, 2021)
The objective of the study was to describe the sociodemographic and clinical profile of users of the Endodontics discipline at the Ponta Grossa State University (UEPG). The quantitative, cross-sectional, retrospective and descriptive study used secondary data from the medical records of the Endodontics discipline at the UEPG for the years 2010 to 2017. Sociodemographic and clinical data were extracted by two researchers using a standardized form. Dental records with insufficient information on the completion of treatment were excluded. The data were described by absolute (n) and relative (%) frequencies. 2,224 records were found, and 73 (3.3%) were excluded. Of the 2,151 medical records included, 100 (4.4%) had no radiographs and 67.6% had good quality radiographs. Assistance occurred more in 2014 (18.1%) and 2016 (15.0%) and less in 2015 (7.8%). The majority of users were aged 20-29 years (25.6%), women (62.2%), married (50.9%), residing in the in the city of Ponta Grossa (99.2%), work in the area of ​​maintenance, repair and general services (30.9%) and had no health problem (78.5%). Infection of the dental pulp by caries was the main reason (87.3%) of the treatment, and the lower right first molar was the most treated tooth (7.4%). The most performed treatment was necropulpectomy (57.0%), in two or more sessions (74.6%), with a duration of treatment of eight days (42.1%). The sociodemographic and clinical profile indicates that young women seek more endodontic treatment. Necropulpectomy was the most performed technical procedure due to extensive carious lesions.